2018
DOI: 10.1007/s00405-018-5232-9
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, randomized, controlled, open-label study to compare efficacy of a mineral-rich solution vs normal saline after complete ethmoidectomy

Abstract: Purposes The purpose of this study was to compare the efficacy of a mineral-rich solution vs normal saline solution (0.9% NaCl) following endoscopic complete bilateral ethmoidectomy. Methods This was a prospective, multicenter, randomized, controlled, open-label trial in subjects suffering from steroid-resistant sinonasal polyposis. Adults performed 4 nasal irrigations of mineral or saline solutions daily for 28 days. Evaluations included subject-reported RHINO quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…83,84 One larger prospective open-label study investigated normal IS vs a mineral-rich IS solution in CRSwNP postcomplete ethmoidectomy and found that adding minerals to the IS solution improved endoscopic and QOL scores in older patients, patients with an initial poor QOL or higher symptom scores, and in smokers. 85 Finally, a recent study compared NI with buffered HS to physiological seawater in patients with CRSwNP post-FESS but further characterized them as eosinophilic (ECRSwNP) and noneosinophilic (NECRSwNP) phenotypes. 86 They found that as a group, there were substantial subjective and objective improvements with NI irrespective of the solution used; however, when patients were stratified based on ECRSwNP and NECRSwNP, the latter group treated with buffered HS experienced a greater improvement in mucosal edema and crusting immediately postoperatively and substantial objective improvement in Lund-Kennedy endoscopic scores and saccharine clearance times.…”
Section: Meta-analyses and Systematic Reviewsmentioning
confidence: 99%
“…83,84 One larger prospective open-label study investigated normal IS vs a mineral-rich IS solution in CRSwNP postcomplete ethmoidectomy and found that adding minerals to the IS solution improved endoscopic and QOL scores in older patients, patients with an initial poor QOL or higher symptom scores, and in smokers. 85 Finally, a recent study compared NI with buffered HS to physiological seawater in patients with CRSwNP post-FESS but further characterized them as eosinophilic (ECRSwNP) and noneosinophilic (NECRSwNP) phenotypes. 86 They found that as a group, there were substantial subjective and objective improvements with NI irrespective of the solution used; however, when patients were stratified based on ECRSwNP and NECRSwNP, the latter group treated with buffered HS experienced a greater improvement in mucosal edema and crusting immediately postoperatively and substantial objective improvement in Lund-Kennedy endoscopic scores and saccharine clearance times.…”
Section: Meta-analyses and Systematic Reviewsmentioning
confidence: 99%
“…Isotonic solutions with slightly alkaline pH optimize trophic and functional recovery of the respiratory epithelium. 2 In chronic rhinosinusitis, saline solutions improve mucociliary clearance 3 without altering commensal bacteria. 4 These actions may aid recovery of the nasal epithelium after viral injury and reduce associated symptoms of rhinitis.…”
Section: What Are the Potential Benefits Of Nl To Covid-19 Patients?mentioning
confidence: 99%
“…8 Nasal lavages are commonly used treatments in the upper respiratory tract infections and can decrease duration of illness in common cold. 3,23,24 Given the potential benefits summarized above, nasal saline irrigation may enhance recovery in patients known to be infected with COVID-19. Patients are currently being recruited to a randomized controlled trial to evaluate the benefits to COVID-19 patients, although no results are yet available.…”
Section: What Are the Potential Benefits Of Nl To Covid-19 Patients?mentioning
confidence: 99%
See 1 more Smart Citation
“…Nasal irrigation is commonly prescribed for the prevention and treatment of URTI symptoms and other sinonasal conditions [ 5 10 ]. It provides mechanical cleaning of nasal content [ 11 ], with rare adverse events [ 12 , 13 ]. It enhances mucociliary clearance thereby reducing the contact time of airborne elements with mucus [ 11 , 14 16 ].…”
Section: Introductionmentioning
confidence: 99%